Financial Viability of the Electricity Sector in Developing Countries : Recent Trends and Effectiveness of World Bank Interventions - Independent Evaluation Group (World Bank, Washington, DC, 2016)
This Independent Evaluation Group (IEG) Learning Product addresses the effectiveness of World Bank interventions during fiscal years (FY) 2000–2015 in supporting client countries for improving the financial performance and long-term viability of their electricity sectors. Like other IEG learning products, this study is a synthesis of evaluation findings, cross-cutting lessons, and good practices from existing IEG evaluations, supplemented with a targeted literature review. This study compiled a comprehensive inventory of World Bank electricity sector investment projects approved during FY2000–2015 that contain components and covenants for improving sector financial performance and viability. IEG conducted a targeted literature survey to compile the latest analysis on electricity sector financial viability in developing countries and compiled the leading electricity utilities’ profitability trends between 2003 and 2013 for a sample of 40 World Bank client countries. The study uses available data to characterize an empirical relationship between sector financial performance and sector outcomes. This study’s analysis shows that most investment loans with financial components and covenants for the electricity sector show a moderately satisfactory or better performance regarding their financial performance objectives. This study book is arranged as follows: second chapter is an overview of developing country electricity sector financial performance and financial viability drivers, and it characterizes the link between financial viability and sector outcomes; third chapter covers the role of investment loans in improving sector financial viability and analyzes their performance; fourth chapter covers the role of development policy operations (DPOs) for improving sector financial viability and analyzes their performance; and fifth chapter summarizes the main findings and lessons from World Bank support for sector financial viability and illustrates them with relevant investment loan and DPO examples.